PERUBAHAN KONDISI SOSIAL DAN EKONOMI RUMAH TANGGA NELAYAN DI KAWASAN TEMPAT PELELANGAN IKAN (TPI) KELURAHAN KARAN AUR KECAMATAN PARIAMAN TENGAH KOTA PARIAMAN PROVINSI SUMATERA BARAT - Nora Nurwita; Lamun Bathara; Darwis ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in April-May 2016 wich is placed in the Kelurahan Karan Aur, Central Pariaman Subdistrict, Pariaman City, West Sumatra Province. This recearch aims to knowing the change in social and economic conditions in the fishermen households at region of Tempat Pelelangan Ikan (TPI) Kelurahan Karan Aur. The method used in this research is method survey with respondents 44 fishermen households. Based on the research results,change in social conditions in the fishermen households at region of TPI Kelurahan Karan Aur that increasing the education of childrens of fishermen, the deterioration of the environment to be around TPI as there are many waters that pooled completed activities in TPI and environment around TPI to stink and the formation of three groups of fishermen, while change in economic conditions in the fishermen households at region of TPI Kelurahan Karan Aur that increasing the income of fishermen household, presence of business opportunities and can obtain alternative employment as open stalls, pedicab driver, seller seawater, washers fish. Keyword : Changes, Social Economic Conditions, Fisherman Households, Region TPI, City Pariaman